The protestant work ethic and vocational preference - Furnham, Adrian [Verfasser]; Koritsas, Eva [Verfasser] (My University, 1990)
"The study examined the relationship between various measures of the Protestant Work Ethic (PWE) and Holland's (1973) hexagonal model of vocational preference which specifies six personality and environmental types. It was predicted that PWE measures would be positively correlated with realistic, enterprising and conventional types but not social investigative or artistic. The hypotheses were supported but the PWE measures, themselves all correlated, were also positively correlated with the artistic type. Implications of these findings for vocational guidance and the assessment of individual differences is discussed." (author's abstract) ((en)) Im Rahmen einer schriftlichen Befragung werden Zusammenhänge zwischen protestantischer Arbeitsethik und Berufspräferenzen untersucht. Die Berufspräferenzen werden dabei an sechs Persönlichkeits- und Milieutypen spezifiziert. Aus den Ergebnissen werden Schlüsse für die Berufsorientierung und die Einschätzung individueller Unterschiede gezogen. (IAB)
Protestantische Arbeitsethik und Berufspräferenzen
Keywords: G Gesellschaftlicher Kontext; G 2.4.2 Lebenskonzepte, -stile, Werte; G 2.4.4 Biografiegestaltung; T 4.2 Psychologie; G 1.3.2.2 Übergänge; G 2.3 Wandel von Arbeit & Wirtschaft; L 5 Beratung & Orientierung; Arbeit; Ethik; Einstellung; Persönlichkeit; Berufsneigung; Berufsorientierung; Quantitative Angaben